An analysis of inter-area transactions and income flow of village economies : a case study from Sri Lanka - Chandrasena, U. A.; Vokes, Richard W. A.; Dias, Hiran D.; Kammeier, Hans Detlef; Canadian International Development Agency (Bangkok : Asian Institute of Technology, 1981)
This study looks into the present structure and processes of development in the village economies , focusing on their transactions and income flows as the specific approach. The data have been collected from two village areas in the Wet Zone of Sri Lanka . The rural areas in the Wet Zone, having higher population densities than the Dry Zone , are opened t0 the outs ide world through large or small scale plantation agriculture which has been the main source of income , while government subsidies are flowing into the hands of most of the low income families . The study shows that the analysis of rural transactions and income flow pattern provides a sound approach to the structure , trends and causes of the existing problems of the villages. The Findings reveal that the income f lows from outside areas are most important in the growth and development of these economies. Further increases in production and productivity of these villages is constrained due to the prevailing structural and institutional characteristics of the their economies . Income from external sources is dependent on factors beyond the control of the villagers. However , the attraction of investment and income from outside have a potential for improving the income and making multiplier effects in the village areas, and can be used to solve their problems t o a larger extent. Most of the present inflows of income accumulate in a few hands who do not have that much interest in investing them in the village. Finally, the study shows that these village areas are significant as a unit for analyzing the transactions and income flows of rural economies. Furthermore if the suit able procedure and the feasible projects are identified , the village areas can be considered a s viable units of the plan implementation. This would have to be supplemented by further investigations into the necessary changes in the spatial and institutional structures of rural areas .
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1981
Keywords: Rural development -- Sri Lanka